Nutritional Value and Sensory Properties of Cookies Prepared from Flour Mixes of Carrot (Daucus Carota), Lupine (Lupinus Perennis) and Barley (Hordeum Vulgare) - Salguero, Herminia Sanaguano; León, R. Angélica Tigre; Morejón, I. Favian Bayas; Cueva, Ma Bernarda Ruilova (European Scientific Journal, ESJ, 2017)
Nutritional value and sensory properties of cookies prepared by the combination of different proportions of carrot flour (CF), lupine flour (LF) and barley flour (BF) blends were analyzed. Eight formulations (F) of cookies were prepared from (F1) Control (100% Wheat flour â€œWFâ€), (F2) 33.33% CF, 33.33% LF and 33.33% BF, (F3) 33.33% CF, 41.66% LF and 25% BF, (F4) 33.33% CF, 25% LF and 41.66% BF, (F5) 33.33% CF, 25% LF and 41.66% BF, (F6) 41.66% CF, 33.33% LF and 25% BF, (F7) 25% CF, 41.66% LF and 33.33% BF, (F8) 41.66% CF, 25% LF and 33.33% BF. Cookies were subjected to analysis as moisture value, crude protein, Vitamin A as well as mineral analysis (potassium, calcium, phosphorus and iron) and evaluated for consumer acceptance by sensory analysis. Cookies prepared from formulation F8 showed high levels of vitamin A, (30UI/100 g), potassium (417.42 mg/100 g), calcium (182.40 mg/100 g) and iron (6.88 mg/100 g) in comparison with the others formulations. In the moisture value, F2 had similar value that the control cookies, The F3, F5 and F7 had high value in crude protein. Sensory evaluation established that cookies prepared with the formulation 8 were more acceptable than cookies prepared from other formulations.